DEVELOPMENT OF INTERACTIVE MULTIMEDIA ASSISTED WEB 2.0 APK USING ARTICULATE STORYLINE 3 TO ENHANCE ECOSYSTEM LEARNING OUTCOMES OF ELEMENTARY SCHOOL STUDENTS - Putra, I Putu Fery Aditya; Artini, Ni Putu Juni; Dewi, Made Sri Astika (STKIP Citra Bakti, 2026)
This study was conducted to develop and assess the validity, practicality, and effectiveness of interactive multimedia assisted by Web 2.0 APK and designed using Articulate Storyline 3 for fifth-grade ecosystem instruction. The research applied a Research and Development (R&D) method through the ADDIE framework, which includes the stages of analysis, design, development, implementation, and evaluation. The participants involved one classroom teacher and 31 fifth-grade students from SD Negeri 1 Pendem. Data were obtained through classroom observations, interviews, questionnaires, expert validation forms, and pretest–posttest assessments. The validation findings revealed that the multimedia achieved a score of 92.97% from the material expert and 98.68% from the media expert, both categorized as highly valid. In terms of practicality, the teacher’s assessment reached 98.68%, while students’ responses obtained 94.44%, resulting in an overall average of 96.56%, which indicates a highly practical category. Moreover, students’ mean achievement scores increased from 68.29 on the pretest to 88.25 on the posttest. These results demonstrate that the developed multimedia effectively enhanced students’ understanding and learning outcomes in ecosystem topics.